The structure, functions and clinical significance of the glymphatic system - Tansu Kuşat; Emrah Sur (Eurasian Journal of Veterinary Sciences)
The glymphatic system is a newly discovered waste cleaning system. It provides active removal of metabolites and soluble proteins from the central nervous system (CNS). This system, formed by Aquaporin- 4 water channels (AQP-4) located on astrocytes and their cytoplasmic extensions, has an unlike perivascular canal network. It is remarkable that this system is active during sleep and cannot acts during the wakefulness process. The functioning of the current system in sleep state and the removal of neurotoxic waste products from the CNS accordingly reveal the importance of the biological requirement for sleep. Since the concept of the glymphatic system is a relatively new concept, we will evaluate its clinical significance in this review by looking at its basic structural elements, functions, and relationship with some certain neurodegenerative diseases. We will give information about some research showing that various diseases causing the functional impairment of the glymphatic system and also which diseases the functional impairment of the glymphatic system may cause.